2019
DOI: 10.25124/jmi.v19i2.2234
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Media Marketing, Word of Mouth, and Effectiveness of Advertising on Brand Awareness and Intention to Buy

Abstract: The purpose of this research is to analyze the direct effect of social media marketing, word of mouth, and the effectiveness of advertising on brand awareness and its impact on intention to buy, either directly or indirectly. The data source of 50 respondents, obtained from the customers who use transportation services in Samarinda. Models using path analysis programs and data are processed through SPSS version 23. Result from this research based on sub-stucture model 1 reveal that social media marketing and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 42 publications
5
44
0
12
Order By: Relevance
“…Momany and Alshboul (2016) indicate a strong link between the social media communication efforts and brand awareness. Other studies point out the positive impact that brand awareness has on purchase intention, for example, Maria, et al, (2019) ;Bilgin, (2018);Ansariet al, (2019); Jamali and Khan, (2018) found that brand awareness positively affects purchase intention. Social media marketing is seen as trendiness component of communication which has a significant effect on brand awareness (Seo, & Park, 2018).…”
Section: Brand Awarenessmentioning
confidence: 97%
“…Momany and Alshboul (2016) indicate a strong link between the social media communication efforts and brand awareness. Other studies point out the positive impact that brand awareness has on purchase intention, for example, Maria, et al, (2019) ;Bilgin, (2018);Ansariet al, (2019); Jamali and Khan, (2018) found that brand awareness positively affects purchase intention. Social media marketing is seen as trendiness component of communication which has a significant effect on brand awareness (Seo, & Park, 2018).…”
Section: Brand Awarenessmentioning
confidence: 97%
“…They recorded that out of 272.1 million Indonesians, uniquely, there are 338.2 million active mobile phone numbers. That number is much larger than the population compared to 175.4 million internet users and those who are active with social media 160 million (Maria et al, 2019). What are the habits of social media activists in Indonesia?…”
Section: Exist In Social Mediamentioning
confidence: 99%
“…Referring to Table 4, it can be concluded overall that H-1 has been rejected, while H-2, H-3, and H-4 are acceptable. This is based on the statistical provisions we adopted from Maria et al (2019). With a significance level, it is evident that SERVQUAL is the most dominant variable among others.…”
Section: Figure 2 Demographic Data For Respondentsmentioning
confidence: 99%